Identification and registration practices in transnational perspective people, papers and practices - About, Ilsen 1975-; Brown, James; Lonergan, Gayle (St. Antony's series, 2013)
"Utilising sources that range from 16th century parish registers to the 21st century supermarket loyalty card, this collection examines the history and development of identification documents and surveillance techniques over the past 500 years. Combining the knowledge of several experts from a variety of disciplines, this volume successfully demonstrates how identification and registration can enable and empower a population, particularly if the interests of the state and population coincide. It also reveals the weakness of states or corporations when dealing with issues such as popular resistance and fraud, despite great leaps forward in the scientific methods of identifying individuals. This important book offers a vital contribution to the literature on a variety of topical subject areas such as biometric identification, immigration control and personal data use, as such it is of interest to students and scholars of civil and human rights amongst other disciplines"..